Determining the Prevalence and Severity of Menopausal Symptoms in Post-Menopausal Women of Eluru, Andhra Pradesh, India, using the Menopause Rating Scale (MRS) - Mediboina, Anjali; Pratyusha, Penumala; Kumar, G. Sravan (International Journal of Medical Students, 2024)
Background: This study aimed to assess the prevalence and severity of menopausal symptoms among women in Eluru, Andhra Pradesh, India, to better comprehend the specific challenges faced by rural women during this transitional phase. Methods: Post-menopausal women who visited the Rural Health and Training Center in Eluru between September-November 2021 and had one year of amenorrhea were included. A face-to-face interview administered a questionnaire to collect socio-demographic details and the Menopause Rating Scale (MRS) which contained 11 questions using a 4-point Likert scale. Microsoft Excel and SPSS-20, with one-way ANOVA test were used for data and statistical analysis. Results: A total of 100 respondents were included, aged between 45-60 years. Majority of the respondents (37%) were aged 45-50 years and were unskilled workers (53%) with a monthly income falling under the upper middle-class category (53%). Additionally, 61% belonged to nuclear families. Using the MRS, joint and muscle pains were the most prevalent symptoms (82%), followed by sleep problems (64%) and anxiety (57%). Heat discomfort was reported least frequently (25%). Age groups and symptom severity were found to be significantly associated, indicating that women between 45-50 years were more likely to experience mild-severe symptoms. Conclusion: This study identified a notable prevalence of menopausal symptoms among women in Eluru; however, limitations included the limited sample size and geographic scope. Retrospective data collection might have introduced recall bias. The study highlights the need for increased awareness and education on menopause. Community-based programs and health centers should be established to address these needs.